2013
DOI: 10.1364/oe.21.016784
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced terahertz emission by coherent optical absorption in ultrathin semiconductor films on metals

Abstract: Abstract:We report on the surprisingly strong, broadband emission of coherent terahertz pulses from ultrathin layers of semiconductors such as amorphous silicon, germanium and polycrystalline cuprous oxide deposited on gold, upon illumination with femtosecond laser pulses. The strength of the emission is surprising because the materials are considered to be bad (amorphous silicon and polycrystalline cuprous oxide) or fair (amorphous germanium) terahertz emitters at best. We show that the strength of the emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 46 publications
0
48
1
1
Order By: Relevance
“…5a, the mobility of electrons is greater than the mobility of holes). When the optical thickness of the beam path within BiVO 4 approaches λ/4, the layer begins to act like an antireflection coating, trapping more light inside the layer and giving rise to more absorption, as we recently observed for several semiconductors on gold substrates [5]. Assuming that the metal behaves like a perfect metal, we calculate that the BiVO 4 thickness for which the coating acts like an antireflection coating at 800 nm is about 71 nm, assuming a refractive-index of 2.9 for the BiVO 4 .…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…5a, the mobility of electrons is greater than the mobility of holes). When the optical thickness of the beam path within BiVO 4 approaches λ/4, the layer begins to act like an antireflection coating, trapping more light inside the layer and giving rise to more absorption, as we recently observed for several semiconductors on gold substrates [5]. Assuming that the metal behaves like a perfect metal, we calculate that the BiVO 4 thickness for which the coating acts like an antireflection coating at 800 nm is about 71 nm, assuming a refractive-index of 2.9 for the BiVO 4 .…”
Section: Resultsmentioning
confidence: 62%
“…When a femtosecond laser pulse is incident on such a semiconductor-metal junction, a transient current is formed in the Schottky depletion layer of the metal/semiconductor interface, which gives rise to the emission of an electromagnetic transient in the THz range. In the past, THz emission from, mostly, conventional semiconductors like gallium arsenide, silicon, germanium, and some unconventional ones, such as cuprous oxide, has been studied [5].…”
Section: Introductionmentioning
confidence: 99%
“…48 The excitation of these surface plasmons could also contribute to the enhancement of THz radiation through depletion field induced second order non-resonant optical rectification. 49 Moreover, internal photoelectric emission of charge carriers from metal into the graphite results in additional transient currents. 50 The photon drag effect in graphene layers near interface can also lead to enhancement of the THz emission.…”
Section: Phase Manipulation Of Terahertz Waves By Work Function Enginmentioning
confidence: 99%
“…This poor THz generation efficiency results from the power loss of the pump laser pulses and of the generated THz pulses in the metal film and from the fact that light is also absorbed in a region of the semiconductor where there is no depletion field. Recently, we showed that the THz emission of inverted structures, ultrathin semiconductor layers deposited on gold, is much stronger [3]. When an optimum thickness of the semiconductor layer is chosen, multiple reflections occur inside the layer which acts as an antireflection coating, increasing the absorption within the semiconducting thin film.…”
Section: Introductionmentioning
confidence: 99%